Dakwah dan Media (Studi Pengelolaan Media Dakwah Berbasis Masjid di Kawasan Wisata Halal Mandalika Lombok Tengah) - Bagas, Muhammad Ali; Heriyadi, Heriyadi; Mu`az, Lalu (Alhadharah: Jurnal Ilmu Dakwah, 2023)
This research focuses on two aspects, namely; regarding the management of mosque-based da'wah media, and the contribution of mosque-based da'wah media. Field research as a research method, using observation, interview and documentation techniques to obtain relevant data. Creswell spiral analysis model is used to analyze the data obtained. The results show that; Tolerance-based media management, a management system that is carried out and pursued as a form of contextualization of da'wah locations; Management based on a cooperative system , this management is carried out because we remember that humans are both personal and social creatures, and even though they are equipped with the mind to meet their own needs, humans cannot live alone without the help of other humans. In another sense, the existence of cooperation will make it easier for administrators or managers to plan and implement programs or activities that will be carried out in accordance with the needs of the local community and tourists who come to visit; Position based management, This position-based management is based on the understanding that to get maximum results in the process of preaching is to have a strong spirit of jihad for the designated corner of preaching. Meanwhile, for the contribution of mosque-based da'wah media, in this research three aspects of contribution were found, namely; contribute to spiritual, material and social aspects.